IMPROVEMENT OF PHYSICAL FITNESS IN TAEKWONDO ATHLETES AT THE PRELIMINARY BASIC TRAINING STAGE (Physical Culture and Sport: Scientific Perspective, 2025)
In the current conditions of high-performance sports development, the issue of improving the effectiveness of athlete training is of particular importance. Taekwondo, as a combat sport that combines technical, tactical, physical, and psychological preparation, requires a comprehensive approach to the training process. Purpose of the study: to enhance the physical fitness of taekwondo athletes at the preliminary basic training stage through the use of acrobatic exercises. Research methods. The study employed theoretical research methods such as analysis, comparison, induction, deduction, systematization, and generalization of scientific and methodological literature; pedagogical testing; pedagogical experiment; and methods of mathematical statistics. The participants were 20 ten-year-old taekwondo athletes at the preliminary basic training stage who had fulfilled the requirements of the second youth sports category and the 7th Kup. They were divided into two equal groups — the control group (CG) and the experimental group (EG), with 10 individuals in each. The physical training program for both groups was based on recommended methods and tools used in sports schools, Olympic reserve youth sports schools, and specialized taekwondo institutions. At the same time, the experimental group additionally included acrobatic exercises in their training sessions. Results. After the formative stage of the pedagogical research, the experimental group showed statistically significant improvements in the following tests: sit-ups from a lying position increased by 10.8 repetitions (p
Keywords: taekwondo; methods; preliminary basic training stage; taekwondo athletes